Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
PsycEXTRA Dataset 2004
DOI: 10.1037/e530022013-001
|View full text |Cite
|
Sign up to set email alerts
|

Police Interviews With Victims And Suspects of Violent and Sexual Crimes; Interviewees' Experiences and Interview Outcomes

Abstract: The police interview is one of the most important investigative tools that law enforcement has close at hand, and police interview methods have changed during the twentieth century. A good police interview is conducted in the frame of the law, is governed by the interview goal, and is influenced by facilitating factors that may affect the elicited report. The present doctoral dissertation focuses on police interviews in cases of very serious crimes of violence and sexual offences. Results reveal crime victims'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 83 publications
(129 reference statements)
3
14
1
7
Order By: Relevance
“…As such, no evidence was found to support the overall arguments made by Holmberg and Christianson (2002) and Kebbell et al (2006) that empathic interviews should be "better" on some measure than non-empathic ones. Of course, this could be due to various factors, including: (1) the relatively low use of empathy in the present study À which is worthy of note in itself; (2) that the definition of empathy put forward in the present study does not capture what Holmberg and Christianson (2002), and Kebbell et al (2006) meant by empathy;and (3) that in the present study, confessions by the suspect were not included in the analysis (contrary to the studies by Holmberg andChristianson, 2002 andKebbell et al, 2006). This was because in England and Wales, where the present study was conducted, police officers do not conduct investigative interviews to obtain confessions (Milne & Bull, 1999).…”
Section: The Presence Of Empathycontrasting
confidence: 69%
See 1 more Smart Citation
“…As such, no evidence was found to support the overall arguments made by Holmberg and Christianson (2002) and Kebbell et al (2006) that empathic interviews should be "better" on some measure than non-empathic ones. Of course, this could be due to various factors, including: (1) the relatively low use of empathy in the present study À which is worthy of note in itself; (2) that the definition of empathy put forward in the present study does not capture what Holmberg and Christianson (2002), and Kebbell et al (2006) meant by empathy;and (3) that in the present study, confessions by the suspect were not included in the analysis (contrary to the studies by Holmberg andChristianson, 2002 andKebbell et al, 2006). This was because in England and Wales, where the present study was conducted, police officers do not conduct investigative interviews to obtain confessions (Milne & Bull, 1999).…”
Section: The Presence Of Empathycontrasting
confidence: 69%
“…This is especially so if those officers involved suffer with vicarious traumatization from accumulated traumarelated events, which could influence their attitudes towards suspects (Pearlman & MacIan, 1993;Saakvitne & Pearlman, 1996). Indeed, Holmberg (2004) found that officers who had been exposed to traumatizing events held more negative attitudes when interviewing suspects of sexual offences, and that stressful event exposure was directly related to police officers' self-reported negative attitudes towards interviewing such suspects À this may well only serve to generate some kind of avoidance to the suspect.…”
mentioning
confidence: 95%
“…Being 'humane' has been found to be a very low priority for police interviewers (Holmberg, 2004), as has empathy, regardless of whether they were interviewing victims or suspects; a finding that is likely to be exacerbated when the crimes are of a particularly serious nature. Indeed, more recent research indicates that police officers find it difficult to adopt a sensitive or humane approach with interviewees accused of particular types of crimes (e.g.…”
Section: Police Officers' Interviewing Skillsmentioning
confidence: 99%
“…Research indicates that police officers often adopt markedly different 'styles' when conducting interviews with suspects, and that their style often depends upon the type of crime a person is suspected of having committed (Holmberg, 2004). Two distinct styles are referred to in the recent literature, namely humane or dominant (see Holmberg & Christianson, 2002;Kebbell, Alison, Hurren, & Mazerolle, 2010;Kebbell, Hurren, & Mazerolle, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Baldwin, 1992;Cherryman & Bull, 2001;Holmberg, 2004;Pearse & Gudjonsson, 1999), The list of tactics was further discussed with two experienced homicide investigators in order to ensure that no relevant tactics would be missing from the list. The tactics were drawn from the literature and books regarding police interview (e.g.…”
Section: Questionnairementioning
confidence: 99%